2020
DOI: 10.1111/1753-0407.13108
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control and risk factors for in‐hospital mortality and vascular complications after coronary artery bypass grafting in patients with and without preexisting diabetes

Abstract: Background The purpose of this study was to investigate risk factors of in‐hospital mortality and vascular complications after coronary artery bypass grafting (CABG), particularly the effect of different glycemic control levels on outcomes in patients with and without previous evidence of diabetes. Methods A total of 8682 patients with and without previous diabetes undergoing CABG were categorized into strict, moderate, and liberal glucose control groups according to their mean blood glucose control level <7.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Continuous intravenous insulin infusions are recommended in clinical guidelines for patients with and without diabetes, those who are critically ill, or those undergoing cardiac surgery 27,28,29 . Our previous study 19 showed that better glucose control (<7.8 mmol/L) could reduce the risk of postoperative complications in patients without diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Continuous intravenous insulin infusions are recommended in clinical guidelines for patients with and without diabetes, those who are critically ill, or those undergoing cardiac surgery 27,28,29 . Our previous study 19 showed that better glucose control (<7.8 mmol/L) could reduce the risk of postoperative complications in patients without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SH in patients without previous diabetes was defined as any two random glucose values >7.8 mmol/L after CABG during an ICU stay 17,18 . The primary outcome was MACEs, including in‐hospital mortality, postoperative AMI, stroke and acute renal failure, as previously reported 19,20 . The secondary outcomes were surgical site infection (SSI) and the length of ICU stay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the association between clinical outcomes and glucose control, patientsʼ glycemic control status was categorized into the following three groups according to MBG after CABG, as we have previously reported [ 7 ]: strict-control group, MBG < 7.8 mmol/L; moderate-control group, MBG from 7.8 to 9.9 mmol/L; and liberal-control group, MBG ≥ 10.0 mmol/L.…”
Section: Methodsmentioning
confidence: 99%
“…Blood glucose fluctuations were more common in patients with strict blood glucose control, resulting in worse outcomes [ 6 ]. Our previous study showed that strict glucose control (< 7.8 mmol/L) was associated with an increased risk of in-hospital mortality in patients with diabetes [ 7 ]. Postoperative glycemic control in diabetic patients undergoing On-pump CABG is challenging for physicians because it depends on both the physicians’ clinical experience and the patients’ response to hypoglycemic therapy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%